A one-year prospective study of colonization with antimicrobial-resistant organisms on admission to a Vietnamese intensive care unit. - Duong Bich Thuy; James Campbell; Nguyen Van Minh Hoang; Truong Thi Thuy Trinh; Ha Thi Hai Duong; Nguyen Chi Hieu; Nguyen Hoang Anh Duy; Nguyen Van Hao; Stephen Baker; Guy E Thwaites; Nguyen Van Vinh Chau; C Louise Thwaites (PLoS ONE, 2017)
There is a paucity of data regarding initial bacterial colonization on admission to Intensive Care Units (ICUs) in low and middle-income countries (LMICs). Patients admitted to ICUs in LMICs are at high-risk of subsequent infection with antimicrobial-resistant organisms (AROs). We conducted a prospective, observational study at the Hospital for Tropical Diseases in Ho Chi Minh City, Vietnam from November 2014 to January 2016 to assess the colonization and antimicrobial susceptibility of Staphylococcus aureus, Escherichia coli, Klebsiella spp., Pseudomonas spp. and Acinetobacter spp. among adult patients within 48 hours of ICU admission. We found the admission colonization prevalence (with at least one of the identified organisms) was 93.7% (785/838) and that of AROs was 63.1% (529/838). The colonization frequency with AROs among patients admitted from the community was comparable to those transferred from other hospitals (62.2% vs 63.8%). Staphylococcus aureus was the most commonly isolated bacteria from nasal swabs (13.1%, 110/838) and the methicillin-resistant Staphylococcus aureus nasal colonization prevalence was 8.6% (72/838). We isolated Escherichia coli from rectal swabs from almost all enrolled patients (88.3%, 740/838) and 52.1% (437/838) of patients were colonized by extended spectrum β-lactamase producing Escherichia coli. Notably, Klebsiella pneumoniae was the most frequently isolated bacteria from the tracheal swabs (11.8%, 18/153). Vietnamese ICU patients have a high rate of colonization with AROs and are thus at risk of subsequent infections with these organisms if good infection control practices are not in place.